Pengaruh Komposisi Bahan Baku dan Lama Waktu Pemasakan terhadap Kekuatan Tarik pada Pembuatan Kertas Seni dari Limbah Batang Jagung dan Kertas Bekas - Enda Apriani (Jurnal Mekanika dan Sistem Termal, 2016)
This research was conducted with the aim to obtain raw materials and cooking time on the optimal papermaking art of corn stalks and waste paper to tensile strength. This study used a chemical process using NaOH as liquor. The variables used are mixtures of raw materials corn stalks (BJ) and waste paper (KB), is 100 : 0; 75 : 25; 50 : 50; 25 : 75 (%) and the cooking time, is 60, 120, 180 (minutes). The optimal results on the composition of raw materials is 25 BJ : 75 KB, and the cooking time for 180 minutes, so that the average tensile strength of 0,554 kgf / mm². Results of surface texture white paper pale, delicate texture, pore small paper, and flexible.